Fabrication of Niclosamide loaded solid lipid nanoparticles: in vitro characterization and comparative in vivo evaluation. (17th November 2018) - Rehman, Maqsood Ur; Khan, Mir Azam; Khan, Waheed S.; Shafique, Muhammad; Khan, Munasib
Abstract: Niclosamide (NCS) is an oral anthelminthic drug having low solubility and hence low bioavailability. Current investigation shows an approach to fabricate solid lipid nanoparticles (SLNs) of NCS and evaluated for pharmaceutical, in vitro and in vivo characterization. NFM-3 showed particle size 204.2 ± 2.2 nm, polydispersity index 0.328 ± 0.02 and zeta potential –33.16 ± 2 mV. Entrapment efficiency and drug loading capacity were 84.4 ± 0.02% and 5.27 ± 0.03%, respectively. Scanning electron microscopy image indicated that particles were nanoranged. DSC and P-XRD results showed change in physicochemical properties of NCS. FT-IR spectra confirmed compatibility between NCS and excipients. The drug release profile showed sustained release (93.21%) of NCS in 12 h. Different kinetic models showed zero-order kinetics and Case-II transport mechanism. Study showed maximum stability at refrigerated temperature. In vivo pharmacokinetic study showed 2.15-fold increase in NCS peak plasma concentration as solid lipid nanoparticle formulation (NFM-3) compared to commercial product while relative bioavailability was 11.08. Results including in vitro and in vivo release studies of NCS confirmed that SLNs system is suitable to improve oral delivery of NCS with increased aqueous solubility, permeability and finally bioavailability.